Analysis of Entrepreneurship Behavior and Business Capital Against Business Success - Nam Hee, Jo; Hendrayaty, Heny; Mulyadi, Hari (KnE Social Sciences, 2020)
This study aims to determine the effect of entrepreneurial behavior and business capital on business success. The research method used is quantitative methods and surveys. The population in this study amounted to 263 people. The technique used to determine the size of the sample under study was proposed by Slovin so that respondents who were sampled in this study were entrepreneurs of Binong Jati knitting centers in Bandung as many as 100 respondents. The data analysis technique used is multiple linear regression. Based on the results of the study, it can be seen that entrepreneurial behavior and business capital simultaneously and partially have a positive effect on business success. Based on the results of the study, the recommendations proposed were that entrepreneurial behavior and business capital must be improved so that business success was achieved. Keywords: Entrepreneurship Behavior, Business Capital, Business Success